Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan di Universitas Panca Sakti Bekasi - Tesmanto, Joni; Rina, Nova (International Journal Administration, Business & Organization, 2022)
This study aims to determine how much influence the work environment has on employee performance at Panca Sakti University Bekasi, Indonesia partially. This research belongs to the type of quantitative descriptive research. The population in this study were all employees at Panca Sakti University Bekasi, totaling 121 employees. The sampling technique is cluster sampling where a portion of the population is used as a sample, totaling 57 people. The analytical method used is simple linear regression analysis, correlation coefficient, t test, and coefficient of determination. The conclusions of this study are, 1) The results of simple linear regression analysis can be seen that the Work Environment variable has a significant influence on employee performance at Panca Sakti University Bekasi this is indicated by the regression value Y = 0.784 + 0.612 which means that the work environment variable has an influence which is significant to employee performance., 2) The correlation coefficient value is 0.648 which lies between -1 0.538 +1. That is, the value of the correlation coefficient (r) indicates that the relationship between the two variables is strong and positive, meaning that the work environment has an effect on improving employee performance. 3) The results of the t-test analysis, obtained by 5.751 while the t-table is 1.458 because t-count is greater than t-table means H0 is rejected and Ha is accepted. 4) Analysis of the coefficient of determination obtained the coefficient of determination of r = 0.319